Strategies for the prevention of bronchopulmonary dysplasia - Dini, Gianluca; Ceccarelli, Sara; Celi, Federica (Frontiers in Pediatrics, 2024)
Bronchopulmonary dysplasia (BPD) is a common morbidity affecting preterm infants and is associated with substantial long-term disabilities. The pathogenesis of BPD is multifactorial, and the clinical phenotype is variable. Extensive research has improved the current understanding of the factors contributing to BPD pathogenesis. However, effectively preventing and managing BPD remains a challenge. This review aims to provide an overview of the current evidence regarding the prevention of BPD in preterm infants, offering practical insights for clinicians.